2014
DOI: 10.3390/atmos5020370
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Precipitation and Convection Occurrence over the Mediterranean Basin Derived from a Decade of Microwave Satellite Observations

Abstract: Abstract:The Mediterranean region is characterized by its vulnerability to changes in the water cycle, with the impact of global warming on the water resources being one of the major concerns in social, economical and scientific ambits. Even if precipitation is the best-known term of the Mediterranean water budget, large uncertainties remain due to the lack of suitable offshore observational data. In this study, we use the data provided by the Advanced Microwave Sounding Unit-B (AMSU-B) on board NOAA satellite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 54 publications
4
20
0
Order By: Relevance
“…While there is less variability over the sea. Alhammoud et al (2014) found a maximum frequency of deep convection over the MB in September-October and a minimum one in June and July, which is consistent with Funatsu et al (2009) and Melani et al (2013).…”
Section: Spatial Distribution Of Deep Convective Precipitation Over Tsupporting
confidence: 89%
See 1 more Smart Citation
“…While there is less variability over the sea. Alhammoud et al (2014) found a maximum frequency of deep convection over the MB in September-October and a minimum one in June and July, which is consistent with Funatsu et al (2009) and Melani et al (2013).…”
Section: Spatial Distribution Of Deep Convective Precipitation Over Tsupporting
confidence: 89%
“…Some of these regions coincide with areas characterized as being vulnerable to heavy precipitation that induces floods over the MR (Harats et al, 2010). Claud et al (2012) and Alhammoud et al (2014) have extended the data set using measurements from the AMSU-B and the Microwave Humidity Sensor instruments onboard additional NOAA satellites. They found that interannual variability of deep convection is strongest along the northern coasts of the MB.…”
Section: Spatial Distribution Of Deep Convective Precipitation Over Tmentioning
confidence: 99%
“…The physics of the phenomenon is complex and depends on the dynamics of rainfall, the changes in rainfall over time, and the characteristics of urban catchment areas with storm overflows. Currently, the annual number of overflows in the catchment areas can be assessed based on long-term observations of their operation (Price, 2000;Andrés-Doménech et al, 2010;Gamerith et al, 2011), but it is a costly solution due to the need for the continuous monitoring of flows. An alternative approach is to build a hydrodynamic model of the catchment, which requires detailed data about the basin, precipitation from a long period (30 years according to the German Association for Water, Wastewater and Waste's (DWA) standard DWA-A 118E, 2006) and flows to calibrate the model from a period of at least 2 years (Szeląg et al, 2016).…”
mentioning
confidence: 99%
“…A similar conclusion was reached by Alhammoud et al . [] who noted that rainfall and specially convective rainfall in ERA‐INTERIM over the Mediterranean Sea were systematically underestimated compared to microwave satellite retrievals. The large dispersion between NWPM, both for heat and water fluxes, suggest the importance of errors and drift affecting model runs, when ocean models are forced with atmospheric NWPM flux fields without any correction [e.g., Sanchez‐Gomez et al ., ; Valdivieso et al ., ].…”
Section: Discussionmentioning
confidence: 99%